The Success of the July Revolution Movement in Overthrowing the Government of Sheikh Hasina in Bangladesh in 2024 - Ibrahim, Surya; Kartini, Evida (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2026)
This study examines the dynamics of the July Revolution Movement that overthrew Sheikh Hasina's government in Bangladesh. The movement emerged after the government reversed its plan to abolish the quota system for descendants of independence fighters in civil service recruitment — a policy widely regarded as discriminatory and as reinforcing political patronage. What began as student protests focused on a specific policy issue grew into demands for Sheikh Hasina's resignation. This study employs a qualitative approach using Braun and Clarke's (2006) deductive thematic analysis method. Political process theory serves as the thematic framework, encompassing three elements: political opportunities, mobilizing structures, and framing processes. The findings indicate that a crisis of legitimacy, military neutrality, and elite opposition support created political opportunities for the movement. Mobilization was led by a student alliance, expanded through digital networks, and supported by civil society. The framing process utilized symbols, art, and social media to build emotional solidarity and reinforce resistance narratives. The interaction of these three elements enabled the movement to drive changes in the power structure, ultimately ending Sheikh Hasina's rule.